2013
DOI: 10.1212/wnl.0b013e3182904f82
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis of standard vs selective temporal lobe epilepsy surgery

Abstract: Standard ATL confers an improved chance of achieving freedom from disabling seizures in patients with TLE. Improved seizure freedom must be balanced against the neuropsychological impact of each procedure. A randomized controlled trial is justified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
167
1
6

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 269 publications
(182 citation statements)
references
References 31 publications
8
167
1
6
Order By: Relevance
“…In a meta‐analysis, anterior temporal lobectomy had an 8% greater seizure freedom rate than transcortical selective amygdalohippocampectomy 61. Amygdalohippocampectomy was associated with better postoperative memory than temporal pole and hippocampal resection 62…”
Section: Scope Of Surgical Treatmentmentioning
confidence: 99%
“…In a meta‐analysis, anterior temporal lobectomy had an 8% greater seizure freedom rate than transcortical selective amygdalohippocampectomy 61. Amygdalohippocampectomy was associated with better postoperative memory than temporal pole and hippocampal resection 62…”
Section: Scope Of Surgical Treatmentmentioning
confidence: 99%
“…Nonetheless, three studies have found better seizure-control in patients submitted to ATL 4,22,23 . Similarly, two recent systematic reviews concluded that ATL is associated with a reduced rate of seizure recurrence compared to SelAH 24,25 . In other words, a consensus on this matter has not yet been reached.…”
Section: Discussionmentioning
confidence: 92%
“…A recent survey of nine major epilepsy surgery centers22 shows that this challenging population of DRE patients with normal MRI currently represents the main patient population presenting for consideration of surgery, and that the proportion of invasive EEG recordings not followed by resections has more than tripled between 1991 and 2011. In an era in which multiple types of invasive EEG are available, including stereo‐EEG, subdural electrodes, and combinations of subdural electrodes and depths, we should rigorously define criteria for choosing which technology to use and when the risk/benefit ratio of such evaluations, especially when invasive, is justified.Selective amygdalohippocampectomy versus traditional temporal lobe resections, particularly in patients with preserved memory function: Limiting the resection of the temporal stem and mesial structures is speculated to optimize neuropsychological outcomes, whereas including these structures in a standard temporal lobe resection is hypothesized by some to be necessary for optimal seizure outcomes 66, 67

Ablative versus resective strategies for temporal and extratemporal epilepsy also need further investigation.

The indications and comparative effectiveness of the different neuromodulatory approaches should be defined.

…”
Section: Gaps In Knowledgementioning
confidence: 99%
“…Selective amygdalohippocampectomy versus traditional temporal lobe resections, particularly in patients with preserved memory function: Limiting the resection of the temporal stem and mesial structures is speculated to optimize neuropsychological outcomes, whereas including these structures in a standard temporal lobe resection is hypothesized by some to be necessary for optimal seizure outcomes 66, 67…”
Section: Gaps In Knowledgementioning
confidence: 99%